Analysis Of The Effect Of Time Management, Budget Management, And Employee Skill Through Quality Project As Mediation Variables To Improve Customer Satisfaction In Luxury Residential Interior Design - Calvin Arandy Gunardi; Damelina Basauli Tambunan (UNIVED Press, 2025)
The purpose of this thesis is to determine the effect of time management, budget management, and employee skills on project quality and customer satisfaction in luxury residential interior design projects. This research was conducted on Arandy Mega Construction (AMC) customers with a population of 55 customers. The research design used quantitative research with a causal research type. Sampling used saturation sampling, which involved the entire population as a research sample. Data collection used questionnaires and data analysis was carried out using SEM PLS analysis. The results of the instrumental test show that each statement representing the research variables in the questionnaire is a valid and reliable statement. The results of the hypothesis test with SEM PLS explain that time management, budget management, and employee skills had a significant positive effect on project quality. The results of the study also showed that project quality had a partial mediation role on the effect of budget management on customer satisfaction, but had a full mediation role on the effect of time management and employee skills on customer satisfaction.